Flame-retardant modified glass fiber, preparation method thereof and application thereof in flame-retardant reinforced polyamide

By aminating the surface of glass fiber and modifying PAPP-co-MPP, combining materials such as nylon and polyamine phosphate, polyamide composite materials with excellent flame retardant and mechanical properties were prepared, and glass in the prior art was solved The problem of flammability of fiber reinforced materials at high temperatures has achieved simultaneous improvement of flame retardant and mechanical properties.

CN119241092APending Publication Date: 2025-01-03CHONGQING COPOLYFORCE NEW MATERIALS CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411372564.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing glass fiber reinforced polymer materials are flammable at high temperatures, and the flame retardant modification is difficult. The addition of a large amount of flame retardant will affect the mechanical properties, making it difficult to optimize the flame retardant and mechanical properties of the material at the same time.

Method used

After dispersing the glass fibers in an alcohol solution, they are further reacted with PAPP-co-MPP to form flame retardant modified glass fibers, and are then combined with nylon, polyamine phosphate, and aluminum organic hypophosphate. Combining materials such as the like, a polyamide composite material with flame retardant modified glass fiber was prepared.

Benefits of technology

It effectively suppresses the "candle wick effect", improves the flame retardant and mechanical properties of polymer/glass fiber composites, reduces the use of flame retardant, and improves the overall performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241092A_ABST
    Figure CN119241092A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of flame-retardant polyamide materials, in particular to flame-retardant modified glass fibers, a preparation method thereof and application of the flame-retardant modified glass fibers to flame-retardant reinforced polyamide. The preparation method of the flame-retardant modified glass fiber sequentially comprises the following steps: dispersing glass fiber in an alcoholic solution, adding an amino coupling agent, and performing activation reaction to obtain aminated glass fiber; and dispersing the aminated glass fiber in an organic solvent, adding the focused piperazine phosphate-melamine polyphosphate random copolymer, and reacting to obtain the flame-retardant modified glass fiber. After the glass fiber is modified, the polymer / glass fiber composite material quickly forms an expanded, compact and hard carbon layer on the surface of the glass fiber at high temperature, so that the candlewick effect is inhibited, and the mechanical property of the composite material can be enhanced at the same time. According to the technical scheme, the technical problem that the mechanical property and the flame retardant property of the glass fiber modified polyamide composite material in the prior art are difficult to optimize at the same time can be solved, and the glass fiber modified polyamide composite material has ideal popularization and application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of flame-retardant polyamide materials, and in particular to flame-retardant modified glass fiber, a preparation method thereof and application of the flame-retardant reinforced polyamide thereof. Background Art

[0002] Glass fiber (GF) is an inorganic non-metallic material with the advantages of high mechanical strength, strong heat resistance, good chemical resistance, and good insulation performance. It is often used as a polymer reinforcement material and can significantly improve the mechanical properties of polymer composites. It is widely used in construction, electronics, transportation, aerospace, and national defense.

[0003] Polymer materials contain a large amount of hydrocarbon elements and are flammable. For polymer composites with added glass fibers (polymer / glass fiber composites), the polymer melt will infiltrate the surface of the glass fiber at high temperatures and generate interfacial tension, producing a "wick effect", that is, the polymer melt will quickly infiltrate, spread and flow through the glass fiber surface to the combustion area, further increasing the fire hazard of the polymer composites, making the flame retardant modification of polymer composites with added glass fibers much more difficult, and limiting their development and application.

[0004] Nylon is an extremely important thermoplastic engineering plastic. Since the industrial production of DuPont in the United States in the 1950s, it has a development history of nearly 50 years and currently ranks first among engineering plastics. Although nylon has excellent properties such as light weight, high strength, corrosion resistance, and strong wear resistance, its defects such as poor wet dimensional stability and low impact strength at low temperatures limit its application in high-end industries. Therefore, people use various methods to modify it. Among them, adding high-performance fibers to the nylon matrix to enhance its mechanical properties is one of the more common means. As early as the 1970s, people used glass fibers or other types of fibers to enhance their performance. In recent years, glass fiber reinforced nylon materials have developed rapidly, because nylon and glass fibers are both excellent materials in the field of engineering plastics. The composite of the two comprehensively reflects their respective advantages. The strength and rigidity are much higher than those of unreinforced nylon, the creep is small, the dimensional accuracy is good, the thermal stability is significantly improved, and the wear resistance and damping properties are excellent. For nylon / glass fiber composite system, most foreign countries currently use nylon 6 or nylon 66 as the matrix material, and short or long (continuous) glass fiber as the reinforcement material. Glass fiber reinforced nylon 6 composite material combines the advantages of both, improves the shortcomings and deficiencies of raw materials, and focuses on improving the mechanical properties and antistatic properties of the material. It has broad application prospects in the fields of automobiles, ships, aerospace, transportation, etc.

[0005] In order to reduce the flammability of glass fiber reinforced polymer materials, the current more widespread solution is to suppress the "wick effect" by adding sufficient high-quality flame retardants to polymer / glass fiber composite materials. However, the addition of a large amount of flame retardants will seriously affect the mechanical properties of polymer materials, resulting in a decrease in the gain effect of glass fiber in polymer materials. Therefore, it is urgent to improve the flame retardant properties of glass fiber reinforced polyamide materials and enhance the flame retardant and mechanical properties of composite materials. Summary of the invention

[0006] The present invention aims to provide a method for preparing flame-retardant modified glass fiber, so as to solve the technical problem in the prior art that the mechanical properties and flame-retardant properties of glass fiber modified polyamide composite materials are difficult to be optimized simultaneously.

[0007] In order to achieve the above object, the present invention adopts the following technical scheme:

[0008] A method for preparing flame retardant modified glass fiber comprises the following steps performed in sequence:

[0009] The glass fiber is dispersed in an alcohol solution, and an amino coupling agent is added under stirring conditions, and after activation reaction, the amino glass fiber is washed and dried to obtain an amino glass fiber; the amino glass fiber is dispersed in an organic solvent, PAPP-co-MPP is added, and after reaction, the flame retardant modified glass fiber is obtained by washing and drying.

[0010] The chemical formula of PAPP-co-MPP is shown in formula (10), where MPP represents formula (8), PAPP represents formula (1), and the mass ratio of PAPP to MPP is 1:0.2-5;

[0011]

[0012] 500<m<10000, 500<n<10000, x>0, y>0, p>0.

[0013] Furthermore, the alcohol solution is an ethanol solution; the usage ratio of the glass fiber and the alcohol solution is 100g:250-750ml.

[0014] Furthermore, the amount of the amino coupling agent is 1-5% of the mass of the glass fiber; and the activation reaction conditions are 60-100° C. for 4-8 hours.

[0015] Furthermore, the organic solvent includes any one of ethanol, water, DMF, DMSO, acetonitrile and an aqueous solution of ethanol; and the usage ratio of the amino glass fiber to the organic solvent is 80-160 g: 200-1000 mL.

[0016] Furthermore, the dosage ratio of PAPP-co-MPP and amino-treated glass fiber is 0.1-5 g:80-160 g; and the reaction conditions of PAPP-co-MPP and amino-treated glass fiber are 20-50° C. and 2-12 h.

[0017] Furthermore, the focused piperazine phosphate is obtained by the following method: dipiperazine phosphate is heat treated for 30-240 min in a nitrogen atmosphere, a pressure environment of 0.05-0.3 MPa, and a condition of 120-320° C. to undergo thermal polymerization and dehydration condensation to obtain the focused piperazine phosphate.

[0018] Furthermore, melamine polyphosphate is obtained by the following method: melamine phosphate is heat-treated for 60-300 minutes under a nitrogen atmosphere, a pressure environment of 0.05-0.3 MPa, and a temperature of 220-360° C. to thermally polymerize and dehydrate to condense into melamine polyphosphate.

[0019] PAPP-co-MPP is obtained by the following method: focusing piperazine phosphate and melamine polyphosphate in a mass ratio of 1:0.2-5, under reaction conditions of 200-280°C, 0.1-1.5MPa, in a nitrogen atmosphere, after 30-180min of reaction, thermal polymerization and dehydration to obtain PAPP-co-MPP;

[0020] Preferably, piperazine phosphate and melamine polyphosphate are focused at a mass ratio of 1:0.5, under reaction conditions of 270° C. and 0.5 MPa, in a nitrogen atmosphere, for 180 min, and then thermally polymerized and dehydrated to obtain PAPP-co-MPP.

[0021] The technical solution also provides a method for preparing a flame-retardant modified glass fiber and a flame-retardant modified glass fiber prepared therefrom.

[0022] The technical solution also provides a polyamide composite material containing flame retardant modified glass fiber, wherein the raw materials include, by weight: 30-80 parts of nylon, 5-60 parts of flame retardant modified glass fiber, 5-20 parts of melamine polyphosphate, 5-20 parts of organic aluminum hypophosphite, 0.5-4 parts of flame retardant synergist, 0.3-2 parts of nucleating agent, 0.5-2 parts of coupling agent, 0.3-3 parts of lubricant, and 0.2-1 parts of antioxidant;

[0023] The preparation method is as follows: nylon, melamine polyphosphate, organic aluminum hypophosphite and flame retardant synergist are added into a mixer, and stirred at room temperature for 5-30 minutes; the temperature of the mixer is increased to 80-180°C, and a coupling agent is added and stirred for 10-30 minutes; after cooling to room temperature, a lubricant, a nucleating agent and an antioxidant are added, and stirred for 5-30 minutes to obtain a premix; the premix is ​​extruded by a twin-screw extruder, and flame retardant modified glass fiber is added by side feeding, the temperature during extrusion is 200-300°C, and then the granular material of the polyamide composite material is obtained by strip drawing and pelletizing, and screening and dehydration.

[0024] In summary, the present invention modifies the surface of glass fiber and coats the macromolecular intumescent flame retardant with excellent carbonization effect on the surface of glass fiber, so that the polymer / glass fiber composite material quickly forms an expanded, dense and hard carbon layer on the surface of glass fiber at high temperature, thereby greatly suppressing the "wick effect". In addition, after the surface of glass fiber is modified with a focused piperazine phosphate-melamine polyphosphate random copolymer (PAPP-co-MPP) with a certain molecular chain, the compatibility of glass fiber and flame-retardant polyamide can be improved, which plays a bridge and anchoring role between glass fiber and other flame retardants / polyamides, thereby improving the mechanical properties of flame-retardant reinforced polyamide. Conventional flame-retardant reinforced polyamides have poor mechanical properties, and glass fibers modified with the surface of focused piperazine phosphate-melamine polyphosphate (MPP) random copolymer can improve the mechanical properties of polyamide. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Schematic diagram of the amino modification and flame retardant modification of the glass fiber of Example 1.

[0026] Figure 2 This is the appearance of the glass fiber surface modified by random copolymer after combustion treatment.

[0027] Figure 3 This is the appearance of glass fiber without surface modification after combustion treatment. DETAILED DESCRIPTION

[0028] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto. Unless otherwise specified, the technical means used in the following examples and experimental examples are conventional means well known to those skilled in the art, and the materials, reagents, etc. used can be obtained from commercial sources.

[0029] Example 1: Preparation process of modified glass fiber

[0030] (1) Focus on the synthesis of piperazine phosphate (PAPP)

[0031] The structure of the focused piperazine phosphate is shown in formula (1), n=500-10000, and it is synthesized from piperazine diphosphate (formula (4)). The synthesis of piperazine diphosphate is a conventional method in the prior art (using a conventional reactor in the prior art), specifically, phosphoric acid (formula (2)) and piperazine (formula (3)) are used in a molar ratio of 2.0-2.2:1, under reaction conditions of 60-150°C and 0.1-1.0MPa (in a reaction system with water or alcohol as solvent), and the reaction is carried out for 30-300 minutes to obtain. The reaction equation is shown in formula (5).

[0032] The piperazine diphosphate obtained and purified by the above-mentioned chemical reaction is heat-treated in a nitrogen atmosphere, a pressure environment of 0.05-0.3 MPa, and a temperature of 120-320° C. for 30-240 min to undergo thermal polymerization, dehydration, and condensation to obtain piperazine phosphate (Formula (1)). The reaction equation is shown in Formula (6).

[0033]

[0034]

[0035] (2) Synthesis of melamine polyphosphate (MPP)

[0036] Using deionized water as solvent, melamine (ME) and H3PO4 are reacted by acid-base neutralization to prepare melamine phosphate (MP) with high purity, high whiteness and high thermal stability, and then MP is subjected to high-temperature thermal polymerization to obtain melamine polyphosphate (MPP). The above synthesis process can be found in the inventor's previously published paper "Zhong Zhiqiang, Synthesis of Melamine Polyphosphate and Properties of Flame-Retardant Polypropylene, Engineering Plastics Application, 2018". Specifically, in this embodiment, the method for preparing melamine phosphate is: the molar ratio of ME to H3PO4 is 1:1.05, the reaction time is 2.0h, the reaction temperature is 95°C, and the molar ratio of ME to deionized water is 3:97. Melamine phosphate (Formula (7)) was synthesized under the above conditions.

[0037] Then, melamine phosphate is used to synthesize melamine polyphosphate (MPP). Melamine phosphate is heat treated at 220-360° C. for 60-300 min, in an inert gas environment (such as nitrogen) and under a pressure of 0.05-0.3 MPa, and thermally polymerized and dehydrated to form melamine polyphosphate (MPP, formula (8), 500<m<10000), and the reaction formula is shown in formula (9).

[0038]

[0039] (3) Focus on the synthesis of piperazine phosphate (PAPP)-melamine polyphosphate (MPP) random copolymer (PAPP-co-MPP)

[0040] Focused piperazine phosphate and melamine polyphosphate are reacted at a molar ratio of 1:0.2-5 under reaction conditions of 200-280°C and 0.1-1.5MPa (nitrogen atmosphere) for 30-180 minutes, and then thermally polymerized and dehydrated to obtain a focused piperazine phosphate-melamine polyphosphate random copolymer (PAPP-co-MPP), the structural formula of which is shown in Formula (10), and the reaction equation of which is shown in Formula (11). The polymerization degrees of focused piperazine phosphate (PAPP, Formula (6)) and melamine polyphosphate (MPP, Formula (8)) are both greater than 500 and less than 10000, that is, 500<m<10000, and 500<n<10000. In Formula (10), x>0, y>0, and p>0, and in PAPP-co-MPP, the mass ratio of PAPP to MPP is 1:0.2-5.

[0041]

[0042]

[0043] (4) Amide modification of glass fiber (GF-NH2)

[0044] Disperse 100g of chopped glass fiber (GF, ECS301CL model glass fiber can be used) in ethanol / water (250-750ml, for example, 450:50 ethanol solution), add 1-5wt% of amino coupling agent (for example, KH550, etc.) under high-speed stirring (200-1500rpm), raise the temperature from room temperature to 60-100℃ and react for 4-8h. After the reaction is completed, filter, wash and dry at 80℃ to obtain GF-NH2.

[0045] (5) Preparation of flame retardant modified glass fiber (GF-NH2-FR)

[0046] GF-NH2 (80-160 g) was dispersed in 200-1000 mL of solvent (ethanol, water, DMF, DMSO, acetonitrile and other organic solvents), PAPP-co-MPP (0.1-5 g) was added to the solution, and the reaction was continued at 20-50 ° C for 2-12 h while maintaining a stirring speed of 50-1500 rpm. After the reaction was completed, GF-NH2-FR was obtained by filtering, washing and drying at 80 ° C.

[0047] The schematic diagram of the synthesis process of steps (4) and (5), the schematic diagram of the amino modification of glass fiber (GF-NH2) and its flame retardant modification (GF-NH2-FR) are shown in detail. Figure 1The glass fiber surface is modified with PAPP-co-MPP, and then the modified glass fiber is burned, and a carbon layer is formed on the surface of the glass fiber (see typical pictures Figure 2 If the glass fiber surface is not modified in any way and the glass fiber is burned, the carbon layer will not appear on the surface of the glass fiber (see the typical picture). Figure 3 ). Figure 2 and Figure 3 Long glass fibers are used in this study. Although this scheme uses short glass fibers to make flame-retardant reinforced composite materials, it is not convenient to intuitively display the PAPP-co-MPP modification effect on short fibers. Therefore, long fibers are used in this experiment to observe the state of glass fibers modified with PAPP-co-MPP after combustion.

[0048] Example 2: Preparation process of flame retardant glass fiber reinforced polyamide

[0049] The flame retardant glass fiber reinforced polyamide composite material comprises the following raw material components in parts by weight: in parts by weight, the raw materials include: 30-80 parts of nylon, 5-60 parts of GF-NH2-FR, 5-20 parts of melamine polyphosphate, 5-20 parts of organic aluminum hypophosphite, 0.5-4 parts of flame retardant synergist, 0.3-2 parts of nucleating agent, 0.5-2 parts of coupling agent, 0.3-3 parts of lubricant and 0.2-1 parts of antioxidant.

[0050] Wherein, nylon includes at least one of nylon 6, nylon 66, nylon 46, nylon 610, nylon 612, nylon 9, nylon 11, nylon 12, nylon 1010, nylon 1012, and nylon 1212. The organic aluminum hypophosphite is aluminum diethylphosphinate; the nucleating agent is BRUGGOLEN P22; the 1% thermal weight loss of melamine polyphosphate is greater than or equal to 360°C, and the specific preparation method thereof is shown in Example 1. The flame retardant synergist is any one or a mixture of anhydrous zinc borate, 3.5-water zinc borate, zinc sulfide, zinc oxide, and zirconium phosphate. The coupling agent is a silane coupling agent, which can be any one or a mixture of silane coupling agents such as aminosilane coupling agent KH-9120, isocyanate silane coupling agent KT-930, epoxy silane coupling agent KH-1006 and KH-9130. The lubricant is one or more of white oil, silicone oil, polyethylene wax, ethylene bis stearamide (EBS), pentaerythritol stearate, silicone and amide wax. The antioxidant includes at least one of antioxidant 168, antioxidant 1010 and antioxidant 1098. The preparation method of GF-NH2-FR (flame retardant modified glass fiber) is shown in Example 1.

[0051] The preparation process is as follows:

[0052] Step 1: Add nylon, melamine polyphosphate, organic aluminum hypophosphite and flame retardant synergist into a mixer and stir for 5-30 minutes at room temperature.

[0053] Step 2: Increase the mixer temperature to 80-180°C, add the coupling agent and continue stirring for 10-30 minutes.

[0054] Step 3: After cooling to room temperature, add lubricant, nucleating agent and antioxidant, and stir for 5-30 minutes to obtain a premix.

[0055] Step 4: extrude the premix by a twin-screw extruder, add GF-NH2-FR by side feeding, the temperature during extrusion is 200-300°C, and then obtain flame-retardant reinforced polyamide granules by strip drawing and pelletizing, screening and dehydration.

[0056] Experimental Example 1

[0057] The flame retardant glass fiber reinforced polyamide composition comprises the following raw material components in parts by weight: 53 parts of nylon (PA66-EPR27), 30 parts of GF-NH2-FR, 5 parts of melamine polyphosphate, 10 parts of aluminum diethylphosphinate, 0.5 parts of zinc sulfide, 0.2 parts of nucleating agent BRUGGOLEN P22, 0.5 parts of coupling agent KH1006, 0.5 parts of ethylene bis stearamide (EBS), and 0.3 parts of antioxidant 1098. In the above formula, the addition amount of the flame retardant is 15% (melamine polyphosphate and aluminum diethylphosphinate).

[0058] Prepared as follows: Add nylon, melamine polyphosphate, organic aluminum hypophosphite and flame retardant synergist into a mixer and stir at room temperature for 30 minutes. Raise the mixer temperature to 150°C, add the coupling agent and continue stirring for 30 minutes. After cooling to room temperature, add lubricant, nucleating agent and antioxidant, stir for 30 minutes to obtain a premix. Extrude the premix with a twin-screw extruder, add GF-NH2-FR through side feeding, the temperature during extrusion is 200-300°C (preferably 220-250°C), and then obtain flame retardant reinforced polyamide granules after drawing and pelletizing, sieving and dehydration. More specifically, the twin-screw extruder is divided into 10 temperature zones, and the temperatures of each temperature zone are 220, 230, 240, 250, 260, 260, 250, 240, 240, 220°C in the order of material movement.

[0059] The melamine polyphosphate used in the above process is prepared as follows: melamine phosphate is synthesized according to the method described in Example 1, and the melamine phosphate is heat-treated at 320°C for 240 min, and is thermally polymerized and dehydrated to melamine polyphosphate (MPP, 500<m<10000) in a nitrogen environment and a pressure environment of 0.15 MPa.

[0060] Phosphoric acid and piperazine are mixed in a molar ratio of 2.05:1, reacted at 80°C and 0.1MPa for 210min in an ethanol aqueous solution environment (ethanol volume fraction 50%, phosphoric acid mass fraction of ethanol aqueous solution can be selected to be 5%-30%, 15% in specific experimental operation), and then purified and dried by conventional methods to obtain the intermediate piperazine diphosphate. The intermediate piperazine diphosphate is heat treated at 290°C and 0.1MPa nitrogen atmosphere for 240min, and thermally polymerized and dehydrated to obtain focused piperazine phosphate (PAPP, 500<n<10000).

[0061] The focused piperazine phosphate obtained in the above steps and melamine polyphosphate were mixed (according to the mass ratio of PAPP:MPP = 1:0.5), and thermally polymerized at 270°C for 180min under a 0.5MPa nitrogen atmosphere to obtain PAPP-co-MPP. After a large number of experimental studies, the PAPP-co-MPP prepared according to the above technical parameters was applied to glass fiber modification, and a polyamide composite material was prepared. The polyamide composite material can obtain more excellent effects in mechanical properties and flame retardant properties, which is the optimal parameter for preparing PAPP-co-MPP for preparing polyamide composite materials for glass fiber modification adopted in this scheme. As a comparison, for example, a polyamide composite material prepared with a mass ratio of PAPP:MPP of 1:0.6 (prepared according to the method of Experimental Example 1 except for the different mass ratios) has a flame retardancy of UL 94 (1.0mm) of V-1 level.

[0062] Disperse 100g GF (ECS301CL-4.5, chopped GF) of glass fiber in ethanol / water (500ml, 450:50), add 1wt% (1g) of amino coupling agent KH550 under high-speed stirring (about 1000rpm), raise the temperature from room temperature to 90℃ for 6h, after the reaction is completed, filter, wash and dry at 80℃ to obtain GF-NH2.

[0063] GF-NH2 (100 g) was evenly dispersed in an ethanol solution (500 ml, 400:100), PAPP-co-MPP (1 g) was added to the solution, and the reaction was continued at 50°C for 11 h (while stirring at about 500 rpm). After the reaction was completed, GF-NH2-FR was obtained by filtering, washing and drying at 80°C.

[0064] Experimental Example 2

[0065] This experimental example is basically the same as the experimental example 1, except that the amount of the flame retardant added is 12% (melamine polyphosphate and diethyl aluminum phosphinate), and the specific formula is: 56 parts of nylon (PA66-EPR27), 30 parts of GF-NH2-FR, 4 parts of melamine polyphosphate, 8 parts of diethyl aluminum phosphinate, 0.5 parts of zinc sulfide, 0.2 parts of nucleating agent, 0.5 parts of coupling agent KH1006, 0.5 parts of ethylene bis stearic acid amide, and 0.3 parts of antioxidant 1098. A flame retardant glass fiber reinforced polyamide composition was prepared according to the above formula.

[0066] Comparative Experiment Example 1

[0067] The flame retardant glass fiber reinforced polyamide composition was prepared in the same manner as in Experimental Example 1, except that an equal amount of untreated chopped GF (same as in Experimental Example 1) was used instead of GF-NH2-FR.

[0068] Comparative Experiment Example 2

[0069] The flame retardant glass fiber reinforced polyamide composition was prepared in the same manner as in Experimental Example 2, except that an equal amount of untreated chopped GF (same as in Experimental Example 1) was used instead of GF-NH2-FR.

[0070] Comparative Experiment 3

[0071] The flame retardant glass fiber reinforced polyamide composition was prepared in the same manner as in Experimental Example 1, except that GF-NH2 was used in an equal amount to replace GF-NH2-FR. The specific preparation method of GF-NH2 is shown in Experimental Example 1.

[0072] Comparative Experiment Example 4

[0073] The flame retardant glass fiber reinforced polyamide composition is prepared in the same manner as in Experimental Example 1, except that an equal amount of PAPP-modified GF (GF-NH2-PAPP) is used instead of GF-NH2-FR. The preparation method of GF-NH2-PAPP is as in Experimental Example 1, except that an equal amount of PAPP-co-MPP in Experimental Example 1 is replaced by focused piperazine phosphate (PAPP), and the preparation method of focused piperazine phosphate is also the same as in Experimental Example 1.

[0074] Comparative Experiment Example 5

[0075] Basically the same as Experimental Example 1, but using MPP-modified GF (GF-NH2-MPP) in equal amounts instead of GF-NH2-FR to prepare a flame-retardant glass fiber reinforced polyamide composition. The preparation method of GF-NH2-MPP is as in Experimental Example 1, except that the PAPP-co-MPP in Experimental Example 1 is replaced by melamine polyphosphate (MPP), and the preparation method of melamine polyphosphate is also the same as that in Experimental Example 1.

[0076] Comparative Experiment Example 6

[0077] The same as in Experimental Example 1, but using PAPP and MPP (random copolymer not formed) modified GF (GF-NH2-PAPP / MPP) in equal amounts instead of GF-NH2-FR to prepare a flame retardant reinforced polyamide composition. The preparation method of GF-NH2-PAPP / MPP is as in Experimental Example 1, except that 1g of PAPP-co-MPP in Experimental Example 1 is replaced by a mixture of PAPP and MPP in a mass ratio of 1:0.5, and the preparation method of focused piperazine phosphate and melamine polyphosphate is also the same as in Experimental Example 1.

[0078] The formula compositions of the experimental examples and comparative experimental examples are summarized in Table 1, and the experimental results are shown in Table 2.

[0079] Table 1: Composition of the formula of the experimental example and the comparative experimental example

[0080]

[0081]

[0082] The flame retardant glass fiber reinforced polyamide composites synthesized in the experimental examples and comparative experimental examples were tested for performance. The performance indicators include flame retardancy test, oxygen index (LOI) test, tensile strength, and notched impact strength. The flame retardancy test was carried out according to Test for Flammability of Plastic Materials for Parts in Devices and Appliances-UL 94. The reference standard for oxygen index (LOI) test is GB / T 2406. The reference standard for tensile strength is GB / T1040. The reference standard for notched impact strength is GB / T1843.

[0083] Table 2: Test results of various properties of flame-retardant glass fiber reinforced polyamide composites synthesized in experimental examples and comparative experimental examples (the experimental results are the average values ​​of three independent repeated experiments)

[0084]

[0085] Experimental Example 1 uses the flame retardant modified glass fiber (GF-NH2-FR) of this scheme. When the flame retardant is added less, a relatively ideal flame retardant effect can be achieved, and the mechanical properties of the material are guaranteed. Experimental Example 2 has a reduced amount of flame retardant (melamine polyphosphate and diethyl phosphinate aluminum) added compared to Experimental Example 1, and the flame retardant performance has a certain decline. Comparative Experimental Example 1 does not use flame retardant modified glass fiber (GF-NH2-FR), but uses ordinary glass fiber without surface modification. Compared with Comparative Experimental Example 1, Experimental Example 2 is similar in flame retardant performance indicators (flame retardancy UL 94), but the amount of flame retardant (melamine polyphosphate and diethyl phosphinate aluminum) added in Experimental Example 2 is less. In the case of less flame retardant addition, Experimental Example 2 can maintain a certain flame retardant effect, which shows that the flame retardant modified glass fiber (GF-NH2-FR) of this scheme has the effect of increasing the flame retardant effect of the composite material, and a smaller amount of flame retardant can be added to the composite material to save flame retardant raw materials and reduce the impact of flame retardant on the performance of the composite material.

[0086] This scheme adopts the scheme of synthesizing random copolymers (PAPP-co-MPP) from piperazine phosphate PAPP and melamine polyphosphate MPP. The surface modification of glass fiber using this new material can enhance the effect of glass fiber on polyamide material, eliminate or inhibit the "wick effect", and enhance flame retardant performance. The glass in comparative experimental example 1 was not modified, the glass fiber in comparative experimental example 3 was only modified by amino group, the glass fiber in comparative experimental example 4 was modified by PAPP, and the glass fiber in comparative experimental example 5 was modified by MPP. The flame retardant properties of these composite materials are not ideal, and there is a relatively large gap between the composite materials synthesized in experimental example 1. In addition, the inventors also tried to use PAPP and MPP for the modification of glass fiber at the same time, but did not synthesize PAPP-co-MPP (Comparative Experimental Example 6), and found that this operation mode has little effect on improving the flame retardant effect of the composite material (comparable to the flame retardant properties of the composite materials of comparative experimental examples 4 and comparative experimental examples 5). From the flame retardant test results of Comparative Experimental Example 1, Comparative Experimental Example 4, and Comparative Experimental Example 5, it can be seen that the combined modification of glass fiber with PAPP and MPP can effectively improve the flame retardant properties of the composite material and produce a certain synergistic effect, and this combined use must be achieved in the form of synthesized random copolymers.

[0087] In addition, based on comparative experimental example 4, the inventors also made the following attempts: focused piperazine phosphate (PAPP) was not directly used for compounding with amino-modified glass fiber, but the PAPP obtained in comparative experimental example 4 was placed in a 0.2MPa nitrogen atmosphere and heat-treated at 270°C for 180min (the same condition as the thermal polymerization to obtain PAPP-co-MPP). Under this condition, PAPP spontaneously copolymerized to a certain extent to form heat-treated PAPP. The heat-treated PAPP was replaced with PAPP-co-MPP in equal amounts to prepare a heat-treated PAPP-modified GF, and then a flame-retardant reinforced polyamide composite material was prepared according to the method of comparative experimental example 4. The flame retardant properties of the composite material were tested, and the flame retardancy UL 94 (3.2mm) was V-0, and the flame retardancy UL 94 (1.6mm) was V-1. It can be seen that even if PAPP is heat-treated, it is difficult to effectively improve the flame retardant properties of the composite material as a whole, which is consistent with the flame retardant material performance of comparative experimental example 4.

[0088] The inventors also tried that on the basis of comparative experimental example 5, melamine polyphosphate (MPP) was not directly used for compounding with amino-modified glass fiber, but the MPP obtained in comparative experimental example 5 was placed in a 0.2MPa nitrogen atmosphere and heat treated at 270°C for 180min (the same condition as the thermal polymerization to obtain PAPP-co-MPP). Under this condition, MPP spontaneously copolymerized to a certain extent to form a heat-treated MPP. The heat-treated MPP was replaced with PAPP-co-MPP in equal amounts to prepare a heat-treated MPP-modified GF, and then a flame-retardant reinforced polyamide composite material was prepared according to the method of comparative experimental example 5. The flame retardant properties of the composite material were tested, and the flame retardancy UL 94 (3.2mm) was V-0, and the flame retardancy UL 94 (1.6mm) was V-2. It can be seen that even if the MPP is heat-treated, it is difficult to effectively improve the flame retardant properties of the composite material as a whole, which is consistent with the flame retardant material performance of comparative experimental example 5.

[0089] It can be seen that only by adopting the method of this scheme to thermally polymerize MPP and PAPP to form a random copolymer can the synergistic effect of MPP and PAPP on the flame retardant effect be achieved. Although MPP and PAPP can form their own copolymers by heat treatment alone, the improvement effect on the flame retardant properties of the composite material is limited because MPP and PAPP cannot coexist.

[0090] The oxygen index (LOI) refers to the minimum oxygen concentration required for a material to burn with a flame in an oxygen-nitrogen mixed gas flow under specified conditions. It is expressed as a numerical value of the volume percentage occupied by oxygen. A high oxygen index indicates that the material is not easy to burn, and a low oxygen index indicates that the material is easy to burn. Comparing the experimental data of Example 1, Comparative Experimental Example 1, Comparative Experimental Example 4, Comparative Experimental Example 5 and Comparative Experimental Example 6, a synergistic effect can be clearly observed in the oxygen index (LOI) index. The addition of PAPP-co-MPP surface modification brings about the gain effect of the oxygen index: 32.5-27.5=5 (Example 1-Comparative Experimental Example 1); the addition of PAPP surface modification brings about the gain effect of the oxygen index: 29.1-27.5=1.6 (Comparative Experimental Example 4-Comparative Experimental Example 1); the addition of MPP surface modification brings about the gain effect of the oxygen index: 28.9-27.5=1.4 (Comparative Experimental Example 5-Comparative Experimental Example 1). It can be seen that the oxygen index gain effect (5) brought about by adding PAPP-co-MPP surface modification is greater than the sum of the oxygen index gain effect brought about by the surface modification of PAPP alone and the oxygen index gain effect brought about by the surface modification of MPP alone (1.6+1.5=3.1). PAPP and MPP produce a synergistic effect of improving the flame retardancy of the composite material in the form of a random copolymer. If PAPP and MPP do not form a random copolymer, the synergistic effect of PAPP and MPP cannot occur.

[0091] The composite material of Experimental Example 1 has significantly improved mechanical properties compared to Comparative Experimental Example 1. Although the glass fiber can be improved to varying degrees by amino modification (Comparative Experimental Example 3), PAPP modification (Comparative Experimental Example 4), MPP modification (Comparative Experimental Example 5), and PAPP and MPP combined modification (without random copolymer synthesis, Comparative Experimental Example 6) (when the glass fiber is not used in Comparative Experimental Example 1), the mechanical property improvement effect after the glass fiber is modified with random copolymer (Experimental Example 1) is more significant. It can be seen that after the surface of the glass fiber is modified with PAPP-co-MPP having a certain molecular chain, the compatibility of the glass fiber and nylon can be improved, which plays a bridge and anchoring role between the glass fiber and other flame retardants / nylon, thereby improving the mechanical properties of its flame retardant reinforced polyamide composite material.

[0092] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. A method for preparing flame retardant modified glass fiber, characterized in that: The method includes the following steps: The glass fiber is dispersed in an alcohol solution, an amino coupling agent is added under stirring, and after activation reaction, the amino glass fiber is washed and dried to obtain the amino glass fiber; the amino glass fiber is dispersed in an organic solvent, PAPP-co-MPP is added, and after reaction, the flame retardant modified glass fiber is obtained by washing and drying. The chemical formula of PAPP-co-MPP is shown in formula (10), where MPP represents formula (8), PAPP represents formula (1), and the mass ratio of PAPP to MPP is 1:0.2-5; 500<m<10000, 500<n<10000, x>0, y>0, p>0.

2. The method for preparing a flame retardant modified glass fiber according to claim 1, characterized in that: The alcohol solution is an ethanol solution; the usage ratio of the glass fiber and the alcohol solution is 100g:250-750ml.

3. The method for preparing a flame retardant modified glass fiber according to claim 2, characterized in that: The dosage of the amino coupling agent is 1-5% of the mass of the glass fiber; the activation reaction conditions are 60-100° C. for 4-8 hours.

4. The method for preparing a flame retardant modified glass fiber according to claim 3, characterized in that: The organic solvent includes any one of ethanol, water, DMF, DMSO, acetonitrile and ethanol aqueous solution; the usage ratio of the amino glass fiber and the organic solvent is 80-160g:200-1000mL.

5. The method for preparing a flame retardant modified glass fiber according to claim 4, characterized in that: The dosage ratio of PAPP-co-MPP and amino-treated glass fiber is 0.1-5g:80-160g; the reaction conditions of PAPP-co-MPP and amino-treated glass fiber are 20-50°C and 2-12h.

6. The method for preparing a flame retardant modified glass fiber according to claim 5, characterized in that: The focused piperazine phosphate is obtained by the following method: piperazine diphosphate is heat treated for 30-240 min in a nitrogen atmosphere, a pressure environment of 0.05-0.3 MPa, and a condition of 120-320° C. to obtain the focused piperazine phosphate by thermal polymerization and dehydration condensation.

7. The method for preparing a flame retardant modified glass fiber according to claim 6, characterized in that: The melamine polyphosphate is obtained by the following method: melamine phosphate is heat-treated for 60-300 minutes under a nitrogen atmosphere, a pressure environment of 0.05-0.3 MPa, and a temperature of 220-360° C. to thermally polymerize and dehydrate and condense to obtain the melamine polyphosphate.

8. The method for preparing a flame retardant modified glass fiber according to claim 7, characterized in that: PAPP-co-MPP is obtained by the following method: focusing piperazine phosphate and melamine polyphosphate in a mass ratio of 1:0.2-5, under reaction conditions of 200-280°C, 0.1-1.5MPa, in a nitrogen atmosphere, after 30-180min of reaction, thermal polymerization and dehydration to obtain PAPP-co-MPP; Preferably, piperazine phosphate and melamine polyphosphate are focused at a mass ratio of 1:0.5, under reaction conditions of 270° C. and 0.5 MPa, in a nitrogen atmosphere, for 180 min, and then thermally polymerized and dehydrated to obtain PAPP-co-MPP.

9. The flame retardant modified glass fiber prepared according to the method for preparing a flame retardant modified glass fiber according to any one of claims 1 to 8.

10. A polyamide composite material containing the flame retardant modified glass fiber according to claim 9, characterized in that: The raw materials include, by weight: 30-80 parts of nylon, 5-60 parts of flame retardant modified glass fiber, 5-20 parts of melamine polyphosphate, 5-20 parts of organic aluminum hypophosphite, 0.5-4 parts of flame retardant synergist, 0.3-2 parts of nucleating agent, 0.5-2 parts of coupling agent, 0.3-3 parts of lubricant, and 0.2-1 parts of antioxidant; The preparation method is as follows: nylon, melamine polyphosphate, organic aluminum hypophosphite and flame retardant synergist are added into a mixer, and stirred at room temperature for 5-30 minutes; the temperature of the mixer is increased to 80-180°C, and a coupling agent is added and stirred for 10-30 minutes; after cooling to room temperature, a lubricant, a nucleating agent and an antioxidant are added, and stirred for 5-30 minutes to obtain a premix; the premix is ​​extruded by a twin-screw extruder, and flame retardant modified glass fiber is added by side feeding, the temperature during extrusion is 200-300°C, and then the granular material of the polyamide composite material is obtained by strip drawing and pelletizing, and screening and dehydration.

Citation Information

Cited By

  • Piperazine pyrophosphate-based ultra-dispersed flame-retardant master batch and flame-retardant plate

    CN120718305A